Introducing Disruptive Technology to Criminal Sanctions: Punishment by Computer Monitoring to Enhance Sentencing Fairness and Efficiency - Bagaric, Mirko (2019)
The United States criminal justice system is the most punitive on earth. The total correctional population is nearly seven million, equating to a staggering one in thirty-eight adults. Most of the correctional population comprises offenders who are on parole or probation, and a high portion of these defendants who are on parole or probation reoffend during the sanction period. There has been a growing consensus among lawmakers and the wider community that reforms need to be implemented to reduce the cost of criminal sanctions and to improve their effectiveness. For example, the United States Sentencing Commission has recently proposed an amendment to increase the availability of sentences as alternatives to incarceration. Yet, with little hint of exaggeration, the sentencing system remains in a primitive state when it comes to adopting technological advances. This article seeks to address this failing as a means of overcoming the main shortcomings of current common criminal sanctions. Forty years ago, it was suggested that the most effective way to deal with crime was to assign a police officer to watch over each offender’s every move. The proposal was dubbed “cop-a-con,” and was unviable due to its excessive costs. Yet, technological advances now make this concept, or a similar concept, achievable in a cost-effective manner. This article argues that the sanctions that are currently utilized to deal with the most serious offenders—namely imprisonment, probation, and parole—can be replaced with technological monitoring, which can more efficiently, effectively, and humanely achieve the appropriate objectives of sentencing. Technological disruption in the criminal justice sector is not only desirable, but it is also imperative. Financial pressures and normative principles mandate that the United States can no longer remain the world’s most punitive nation. This article proposes a monitoring sanction using technological advances. This solution has the potential to more efficiently and economically impose proportionate punishment than current probation and parole systems do, while enhancing public safety